On the loose - Janzen, Tara (A Dell book, 2007)
A secret operative with a reputation for remaining cool under pressure, ex-DEA agent C. Smith Rydell finds his abilities under fire when he is assigned to protect gorgeous blonde Honey York, a woman whom Rydell had caught smuggling cash into El Salvador and who has her own agenda for wanting to enlist his personal assistance.